Enhanced power quality in PV integrated EV fed microgrid using intelligent controller - D. Balasubramanyam; G. G. Raja Sekhar; T. Vijay Muni (Institute of Advanced Engineering and Science, 2026)
The need for electric cars (EVs) is steadily rising in the world due to the rise in emissions like CO2 and environmental effects brought on by conventional automobiles. EVs have also transformed the transportation industry. These days, EVs are popular because of their special qualities, which include lower noise pollution, carbon emissions, and operating expenses, as well as the capacity to operate in both grid-to-vehicle (V2G) and vehicle-to-grid (V2G) scenarios. Nevertheless, it affects the power distribution grid in a number of ways. There are various power concerns owing to the introduction of EVs in the distribution system, like instability of voltage, distortions in currents, harm onic distortions, power factor degradation, and fluctuations in voltage. The primary emphasis of this study is on mitigating PQ issues like harmonics produced in the distributed power network when electric vehicles are integrated at the distribution end. In order to reduce harmonics and enhance the distribution side's current profile, a dynamic active power filter (DAPF) with PSO-tuned ICC control technique is introduced. Performance of PSO-DAPF is validated with the help of MATLAB/Simulink, along with V2G and V2G operation.